Identification of antioxidants in Lamiaceae vegetables by HPLC-ABTS and HPLC-MS - Prommajak T. (2017)
Antioxidants in five Lamiaceae vegetables, namely lemon balm, sweet basil, clove basil, holy basil, and lemon basil, were identified by HPLC-ABTS and HPLC-MS. The major antioxidants in the samples were hydroxycinnamic acids. Rosmarinic acid exhibited the highest antioxidant activity in each sample, except clove basil, in which chicoric acid contributed the highest antioxidant activity. Lemon balm had the highest concentration of rosmarinic acid. Chicoric acid (highest in clove basil) and dihydroxy-dimethoxyflavone (highest in basil) were also important antioxidants in many Ocimum spp. Other minor antioxidants were caffeic acid, caftaric acid, syringic acid, syringic acid, rutin, and acacetin-acetylglucoside.